2020
DOI: 10.26434/chemrxiv.12730553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Hydride Conductivity in Layered Perovskites via Crystal Engineering

Abstract: Hydride ion conduction in layered perovskites is of great interest for sustainable-energy applications. In this report we study Ba2ScHO3, a recently synthesized oxyhydride with an unusual anion ordering, using a multifaceted density functional theory approach involving both transition state calculations and molecular dynamics simulations. Beyond simply identifying the key ion migration pathways, we perform detailed analysis of transition states and identify key interactions which drive trends in ionic mobility… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Oxide ion conductivity has been investigated much more thoroughly than hydride ion conductivity, a much more recently observed phenomenon that has so far been restricted to a small number of recent studies of metal hydrides and oxyhydrides. We have recently studied hydride transport in Ba 2 ScHO 3 , a recently synthesised oxyhydride with an unusual anion ordering, examining with DFT the minima in the energy landscape and the transition states between them and also carrying out ab initio molecular dynamics simulations [88]. Ionic mobility depends on the hydride-oxide disorder but activation energies to migration do not; understanding how the migration energies depend on local structural flexibility has allowed us to predict that Sr 2 ScHO 3 will have larger conductivity than the Ba analogue.…”
Section: Fast-ion Conduction -Lamox Bi 2 O 3 and Bimevoxmentioning
confidence: 99%
“…Oxide ion conductivity has been investigated much more thoroughly than hydride ion conductivity, a much more recently observed phenomenon that has so far been restricted to a small number of recent studies of metal hydrides and oxyhydrides. We have recently studied hydride transport in Ba 2 ScHO 3 , a recently synthesised oxyhydride with an unusual anion ordering, examining with DFT the minima in the energy landscape and the transition states between them and also carrying out ab initio molecular dynamics simulations [88]. Ionic mobility depends on the hydride-oxide disorder but activation energies to migration do not; understanding how the migration energies depend on local structural flexibility has allowed us to predict that Sr 2 ScHO 3 will have larger conductivity than the Ba analogue.…”
Section: Fast-ion Conduction -Lamox Bi 2 O 3 and Bimevoxmentioning
confidence: 99%
“…As a result, there may be an intermediate region in which half of the unit cell adopts CsCl ordering, while the other half retains rock salt ordering. The primary motivation for studying these materials is their ability to act as hydride anion conductors, and a previous computational study has shown that the principal anion conduction mechanism in Ba 2 ScHO 3 changes under pressure, from an interstitial-mediated pathway to one involving vacancies 19 via a "bottleneck" transition state that has been observed in other hydride conductors. 21,22 The identification of materials with new hydride ordering patterns is, therefore, an important step in the study of novel hydride-ion conductors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Our calculated activation barrier for hydride diffusion is lower than the measured barrier in LaHO, 34 the most conductive oxyhydride known. Among hydride conductors studied to date, SLHN is relatively unique in that interstitial hydrogen (rather than the hydrogen vacancy) is the primary defect driving the hydride migration; another example is the oxyhydride Ba 2 ScHO 3 , 35,36 in which equal mobility for hydride vacancies and interstitials has been predicted. We also use our methodology to assess the energetics of oxygen incorporation, highlighting the need to protect the material from oxygen.…”
Section: ■ Introductionmentioning
confidence: 99%